2019
DOI: 10.22460/project.v2i3.p275-281
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Peer Editing to Improve Students’ Writing Skill

Abstract: This research aimed at improving students’ skills of writing for the eleventh grade students of SMK TI Pembangunan Cimahi through the use of peer editing. It is expected that peer editing can be used to improve the students’ writing skill in recount text in SMK TI Pembangunan Cimahi. This research was an action research study that consisted of two cycles. In doing the research, the researcher involved 33 students of Class XI as the respondent of the research. The data was collected by observation and writing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
3
1
0
Order By: Relevance
“…Peer-editing was of substantial significance in the module. The current research findings support previous findings which revealed that peer-editing enabled students to learn from other students' writing errors and reinforce their learning as well (Siliwangi, 2019;Yüce, 2019;Harutyunyan & Poveda, 2018;Ekmekci, 2017;Min & Xuemei, 2016). The findings of the present research conform to previous studies' results which addressed the significance of supplementary materials for EFL learners (Cahyaningrum et al 2015;Thankur, 2015;Dodd et al 2015;Saragih, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Peer-editing was of substantial significance in the module. The current research findings support previous findings which revealed that peer-editing enabled students to learn from other students' writing errors and reinforce their learning as well (Siliwangi, 2019;Yüce, 2019;Harutyunyan & Poveda, 2018;Ekmekci, 2017;Min & Xuemei, 2016). The findings of the present research conform to previous studies' results which addressed the significance of supplementary materials for EFL learners (Cahyaningrum et al 2015;Thankur, 2015;Dodd et al 2015;Saragih, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Peer-editing is deemed one of the salient activities in the writing classroom. Peer editing enhances students' writing skills as it enables them to explicitly or implicitly comment on their peers' writing production so they can reinforce their writing skills and contribute to developing other students' writing as well (Siliwangi, 2019;Yüce & Aksu Ataç, 2019;Harutyunyan & Poveda, 2018;Ekmekci, 2017;Min & Xuemei, 2016).…”
Section: Editingmentioning
confidence: 99%
“…Students also chose suitable and varied vocabulary in writing the letter. These findings were in line with a study by Sari and Wati (2019) that found the use of peer-editing techniques improved students' writing on text structure. It was also in line with a study by Nugroho (2020) that found the use of peerediting techniques could improve students writing skill in writing a text with correct grammar and varied vocabulary.…”
Section: Figure 2_ Errors Found In Cycle I and Cycle Iisupporting
confidence: 90%
“…Indonesian EFL learners generally have difficulties in writing the analytical exposition text (Zuana, 2020, Engladesta, 2020. In addition, Fajri, Inderawati, and Mirizon (2015) share the similar findings that students still face some difficulties when they had to produce a text. The problems are caused by lack of grammar, vocabulary and grammatical pattern of a certain text.…”
Section: Introductionsupporting
confidence: 66%